2020
DOI: 10.3390/molecules25081767
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Ultrasound-Assisted Extraction Using Response Surface Methodology for Simultaneous Quantitation of Six Flavonoids in Flos Sophorae Immaturus and Antioxidant Activity

Abstract: Ultrasound-assisted extraction (UAE) was applied to extract rutin (RU), nicotiflorin (NI), narcissoside (NA), kaempferol (KA), isorhamnetin (IS), quercetin (QU), and total flavonoids of Flos Sophorae Immaturus (TFFSI) from Flos Sophorae Immaturus (FSI). Through single factor test and response surface methodology (RSM), the optimal extraction conditions were concluded as follows: ethanol concentration 70%, time 30 min, temperature 61 °C, and liquid/solid ratio 15.30 mL/g, respectively. The actual extraction rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 43 publications
2
23
1
1
Order By: Relevance
“…It is better than other response surface designs due to lower costs of carrying out experimentation and more valid experimental design [30,31]. Many researches have indicated that RSM is a helpful technique to optimize conditions for the encapsulation formulation [32][33][34], and the principal advantage of employing RSM is that it demands few experimental runs to establish the dependence between variable parameters and response values [35,36]. Thus, our work mainly aimed to assess the effects of β-CD/LCEO ratios, preparation temperature, and time on the yield of inclusion complex by applying RSM based on BBD.…”
Section: Introductionmentioning
confidence: 99%
“…It is better than other response surface designs due to lower costs of carrying out experimentation and more valid experimental design [30,31]. Many researches have indicated that RSM is a helpful technique to optimize conditions for the encapsulation formulation [32][33][34], and the principal advantage of employing RSM is that it demands few experimental runs to establish the dependence between variable parameters and response values [35,36]. Thus, our work mainly aimed to assess the effects of β-CD/LCEO ratios, preparation temperature, and time on the yield of inclusion complex by applying RSM based on BBD.…”
Section: Introductionmentioning
confidence: 99%
“…The DPPH radical scavenging ability of the three compounds increased with the concentration, as shown in Figure 5 . The IC 50 value indicates the concentration of the corresponding compound when the scavenging rate reaches 50% [ 41 ]. The IC 50 values of compounds II and III were 0.0497 and 0.1111 mg/mL, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…According to the method in [ 41 ], the antioxidant capacity of the three target compounds was evaluated with minor modifications. Compounds I–III were serially diluted at concentrations of 0.01, 0.02, 0.04, 0.05, 0.08, 0.1, and 0.2 mg/mL in ethanol, which were used as sample solutions.…”
Section: Methodsmentioning
confidence: 99%
“…The roasting process was further optimized by three-levelthree-variable BBD (Table 1), using TFCs as the response values (Fan et al, 2020;Zoubi et al, 2021). Three factors were studied namely reaction time (min, A), reaction temperature (°C, B), and glucose supplement (100%, C).…”
Section: Response Surface Optimization Of the Roasting Methodsmentioning
confidence: 99%